THE MIND OF HOMO NEANDERTHALENSIS (VERUM: Journal of Scientific Initiation, 2026)
This article covers a discussion based on the hypothesis of autism spectrum disorder (ASD) among homo neandertalensis, observing the correspondences between social interactions and their organizations, cognitive rigidity, behavior patterns, brain development and the diagnostic characteristics of the disorder. The analysis is based on recent genetic studies, carried out by Alysson Muotri, who added to stem cells, in the process of cultivating organoids (mini-brains), the editing of the nova 1 gene, which resulted in a significantly modified structure, presenting functioning corresponding to that of a Neanderthal brain, however, which corroborates aspects of a brain diagnosed with autism in modern times. When observing the modified structures, although the research points to arguments that attest that the Neanderthal population is mostly autistic, considering possible differences in neurological development associated with genetic factors and the absence of “central coherence”, a characteristic inherent to ASD, in addition to notable technical stability and low cultural fluidity, it considers that there are several limitations to this interpretation, including the need to have effective communication and cooperation to survive in hostile environments and collective activities. The study also addresses environmental factors and the possible influence of exposure to lead over many years, which may have resulted in problems linked to memory and learning, and may contribute to the hypotheses raised during the research. Furthermore, the insufficiency of genetic and archaeological data to support this hypothesis conclusively is also highlighted and problematized. Finally, in the study, it is concluded that, although there are similarities between Neanderthal characteristics and ASD, there is still insufficient evidence to affirm that this condition has a Neanderthal origin. It is more acceptable to understand these characteristics found as part of the evolution of homo existence.
Keywords: Neuroscience; Autism; Neanderthals